2022
DOI: 10.1155/2022/3944810
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Land Cover and Land Use Change Dynamics in Kibwezi Watershed, Kenya

Abstract: Land use and land cover (LULC) parameters influence the hydrological and ecological processes taking place in a watershed. Understanding the changes in LULC is essential in the planning and development of management strategies for water resources. The purpose of the study was to detect changes in LULC in the Kibwezi watershed in Kenya, using geospatial approaches. Supervised and unsupervised classification techniques using remote sensing (RS) and geographical information system (GIS) were used to process Lands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 19 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…(Murty, 1994). Several studies have been carried out to understand geoenvironmental issues and river basin management (Yurova & Shirokova, 2020;Rotaru, 2010;Bird et al, 2010;Kolesnikova, 2020;Ruttoh et al, 2022;Bufebu & Ilias, 2021). These studies revealed that the complex and dynamic land use and land cover change at various scales have environmental implications.…”
Section: Introductionmentioning
confidence: 99%
“…(Murty, 1994). Several studies have been carried out to understand geoenvironmental issues and river basin management (Yurova & Shirokova, 2020;Rotaru, 2010;Bird et al, 2010;Kolesnikova, 2020;Ruttoh et al, 2022;Bufebu & Ilias, 2021). These studies revealed that the complex and dynamic land use and land cover change at various scales have environmental implications.…”
Section: Introductionmentioning
confidence: 99%